The infinity of science. Theory of everything. - Sultan, Ahmed (IJRDO-Journal of Applied Science, 2016)
Theory of everything is the theory that fully explains and links together all physical aspects of the universe. Theory of everything is one of the major unsolved problems in physics (1). There is a philosophical debate within the physics community as to whether a theory of everything deserves to be called the fundamental law of the universe or not (2). In my theory, I have explained all physical aspects of the universe. I have explained and linked together all the forces that exist in the universe such as strong nuclear forces, weak nuclear forces, electromagnetic forces, gravity, dark matter and dark energy. Infinity may have a defined value if it has a definite unit. For example, if we divide one by infinity 1/∞, it will equal one. That is because the unit of one consists of infinity of complex numbers. If we add together these infinity of complex numbers, it will equal that one. When I want to express the term energy I should choose two logical, comparable and variable factors. In my theory, I choose the volume and the speed of transportation of movement to express the term energy. As when volume decreases, the speed of transportation of movement will increase. And vice versa, when volume increases, the speed of transportation of movement will decrease. Volume can be reduced until reaching the infinity of speed and volume can be increased until reaching the infinity of volume. Then the universe has been formed by interaction between these two infinities in a definite unit, which is the universe. Thus, the two infinities will have defined values.